S86 The anti-inflammatory effects of pneumolysin. (12th November 2015) - Periselneris, JN; James, T; Noursadeghi, M; Brown, JS
Abstract : The inflammatory response to bacteria requires the interaction of pattern recognition receptors with bacterial surface constituents, and humans deficient in components of inflammatory signalling pathways such as IRAK4 are prone to invasive pneumococcal disease. Pneumolysin is a well-recognised virulence factor for Streptococcus pneumoniae that has multiple effects on the host immune response that are primarily thought to be pro-inflammatory; including causing IL1β release due to pore formation, and epithelial cell layer breakdown. We hypothesised that pneumolysin deficient TIGR4 (a serotype 4 strain) would induce less inflammatory cytokines than wildtype from human monocyte derived macrophages. While both pore forming and non-cytolytic purified pneumolysin induced dose dependent inflammatory cytokine release, the pneumolysin deficient bacteria induced greater TNF and IL6 than wildtype, by qPCR and ELISA measurement of protein. This was reduced by inhibition of phagocytosis with cytochalasin D. Given the pore forming effects of pneumolysin we assessed whether differential cell death contributed to the differences in inflammatory response. While wildtype bacteria caused more cell death at 24 h, inhibition of caspases had no effect on the cytokine response suggesting that apoptosis pathways don't directly influence the early inflammatory response. Transcriptome analysis confirmed increased pro-inflammatory and interferon gene signalling with the mutant strain, with reduction of the inflammatory and interferon signature with inhibition of phagocytosis. Wildtype bacteria induced less NFκB translocation, but more IRF3 translocation than Δply. An in vivo intranasal mouse infection showed wildtype was more virulent, with more bacteria recovered from bronchoalveolar lavage fluid at 4 h. However, this was associated with reduced TNF compared to Δply. Neutralising TNF intranasally abrogated the difference in bacteria recovered between wildtype and Δ ply. Thus, the early inflammation dampening effects of pneumolysin released within the phagolysosome may be an important contribution to its virulence by allowing bacterial replication at mucosal surfaces. This may be due to IRF3 mediated inhibition of inflammatory cytokine transcription. Better understanding of the biology of pneumolysin may aid in adjuvant treatment o f S. pneumoniae.